Mapping African Student Affairs Research during the Past Interlude (2008-2019) through Bronfenbrenner’s Lens (Journal of Student Affairs in Africa, 2022)
The research question we pursued was: What are the variations in the themes of research in the African higher education context that will enable researchers to promote student development? This contribution addresses three aspects of student affairs research in the African higher education context. First, it commences with tracing the African position with a document analysis of 121 student affairs research articles published in 34 peer-reviewed journals over the past interval (2008-2019). Secondly, the thematic categorization of the Council for the Advancement of Standards in Higher Education (CAS 2019) was used to determine international publication trends as derived from this document analysis. Thirdly, we applied Bronfenbrenner’s Person-Process-Context-Time (PPCT) model, as an appropriate umbrella research design and guiding framework to review the mapping of African student affairs research. From a comparison between the international CAS categorization and the African categorization, it was concluded that the CAS mapping was largely confirmed by the African analysis, with nine main themes as the foci. Additionally, it was found that four first-hand African themes have not found in the CAS categorization, and significantly limited research was conducted into post-graduate programmes and services (hereafter referred to as PGP's, despite the demands for increased enrolments. The findings suggest that more accurate and continuous mapping of the field can assist policymakers, managers and student affairs practitioners in making more informed choices on supporting growth and development in African higher education, with special emphasis on postgraduate students.
Keywords: African student affairs; research themes; Bronfenbrenner’s Person-Process- Context-Time (PPCT) model; Council for the Advancement of Standards in Higher Education (CAS); post-graduate research and studies; African Higher Education research